دور الموارد البشرية في تعزيز الأمن الغذائي والتنمية الفلاحية المستدامة - مطروح لباس (My University, 2026)
ملخص الأطروحة يرتبط استقرار المجتمعات البشرية وتطورها بقدرها على تنظيم المعرفة وتطبيق المهارات في مختلف الأنشطة. وهو ما وضع المورد البشري في مقام الفاعل الأول لبناء الحضارات وتطوير الأنشطة الاقتصادية بمختلف أنواعها، ولعل القطاع الفلاحي هو الميدان الأكثر احتياجاً لهذا المورد في ظل التحديات المعاصرة المتعلقة بالأمن الغذائي والنمو السكاني ومختلف التحديات والضغوط البينية إن الانتقال بالمورد البشري من مجرد قوة عاملة تقليدية إلى عنصر إستراتيجي يتطلب إستراتيجية تجمع بين مخرجات البحث العلمي والتأهيل المهني وبين القدرة على إدارة الموارد الطبيعية بكفاءة، خاصة في البيئات التي تمتلك مؤهلات واعدة وتحتاج إلى إدارة عقلانية المواجية التحديات المناخية، حيث يبرز دور المورد البشري في تنقيل السياسات الفلاحية وكفاعل أساسي في تبني التكنولوجيا الحديثة وتوظيفها لتحسين الإنتاجية وضمان استدامة الأنظمة الفلاحية، وتتجلى قيمة الإستثمار في المورد البشري في القدرة على خلق التوازن بين استجابة القطاع الاحتياجات الحاضر الغذائية وبين صيانة حق الأجيال القادمة في الموارد المتاحة، مما يجعل من رفع الكفاءة المينية والعلمية للمورد البشري، سواء في مستويات التنفيذ الميداني أو التخطيط التقني الضمانة الوحيدة لتحقيق التنمية الفلاحية المستدامة وتحويل الأمن الغذائي من هدف نظري إلى واقع ملموس في بعد إستراتيجي يستجيب للمتطلبات الحالية وقادر على مواجهة التقلبات الاقتصادية والتحديات النيلية. Abstract: The stability and development of human societies are linked to their ability to organize kncrowledge and apply skills in various activities, which has made human resources the primary driver of civilization-building and the development of economic activities of all kinds. Perhaps the agricultural sector is the field most in need of this resource in light of contemporary challenges related to food security, population growth, and various envisemeal challenges and pressures, Transforming human resources from a mere traditional labor force imo a strategic asset requires a strategy that combines the outcomes of scientific research and profesional traming with the ability to manage natural resources efficiently, especially in environments with promising potential that require rational management to address climate challenges, where the role of human resources is paramount in implementing agricultural policies and as a key actor in adopting and utilizing modern technology to improve productivity and ensure the sustainability of agricultural systems. The value of investing in human resources lies in the ability to strike a halance between the sector's response to current food needs and the preservation of future generations' right to available resources; This makes enhancing the professional and scientific competence of human resources whether at the levels of field implementation or technical planning the only guanamee for achieving sustainable agricultural development and transforming food security from a theoretical goal into a tangible reality with a strategic dimension that meets current requirements and is capable of withstanding economic fluctuations and environmental challenges
Keywords: الموارد البشرية التنمية الفلاحية المستدامة الأمن الغذائي، الفلاحة الذكية، السياسات الفلاحية. الحسين الإنتاج; Human resources; sustainable agricultural development; food security; smart agriculture; agricultural policies; improving production